Water use, transpiration and crop coefficients for irrigated hedgerow olives grown in Southern Portugal - Santos, Francisco L. (2013)
Olive trees are well adapted to the Mediterranean-type agro-ecosystems of southern Portugal and have traditionally been cultivated in areas with no irrigation. According to the 2009 agricultural census, the olive tree cultivation area was around 336,000 ha, of which 164,000 ha are in the southern province of Alentejo. In this southern region of semi arid Mediterranean climate where the erratic annual precipitation of around 300 to 550 mm is not enough to fulfil crop water requirements when needed, summer irrigation is a necessity to prevent crop water stress and ensure profitable yields. Hundreds of high and also very high tree-density hedgerow orchards of the Spanish cultivar Arbequina have recently been established in the region to take advantage of the European Commission decision 2000/406/CE (Official Journal L 154, 27/06/2000 P. 0033-0033) that allowed the expansion of Portuguese olive tree planting quota to 30,000 ha of new orchards. With enhanced olive production and yield depending on irrigation water supply and management, estimating hedgerow olive orchard water uptake in southern Portugal and appropriately scheduling irrigation have since been the primary concern of researchers, farmers and water resources managers. The objective of this study was to establish relationships between olive transpiration and crop transpiration coefficients of very high tree-density hedgerow orchard grown in Alentejo under well-irrigated treatment A (3.05 mm d-1) and sustained deficit irrigation treatment B (2.12 mm d-1) regimes, to understand and improve their irrigation management. On both treatments, daily transpiration at the stand scale (mm day-1) was obtained by sap flow and by dividing the tree transpiration by the area of the planting pattern. The results were compared to the daily outputs obtained with the Penman-Monteith “big leaf” equation coupled with the Orgaz et al. (2007) specific model of bulk daily canopy conductance (Gc) for unstressed olive canopies. With the Willmott index of agreement IA and the root-mean-square error RMSE above 0.8 and below 0.4 mm d-1, respectively (Willmott, 1982), the synthetic model proved sufficiently precise to be used as an appropriate simulation tool for predicting olive stand transpiration for the region. Crop and stress transpiration coefficients were proposed for both treatments.